A nationwide population-based study on epidemiologic characteristics and treatment patterns of dry eye disease in South Korea - Joon Bo Lee; Jiu Lee; Yeo Kyoung Won; Dong Hui Lim (Scientific Reports)
Abstract This study investigated the prevalence of dry eye disease (DED) and the use of major DED medications in South Korea using data from the Health Insurance Review and Assessment database, a nationwide registry with mandatory enrollment. A total of 6,383,885 individuals from 2016 to 2020 were included, selected annually through stratified random sampling. Patients with DED were identified by the ICD-10 code H04.1 assigned as the primary diagnosis by a clinician. Among the total population, 567,141 were diagnosed with DED, yielding a 5-year prevalence of 8.88%. Prevalence was higher in females (11.52%) than in males (5.92%) and increased with age, reaching 21.96% in individuals aged 70–74. Among DED patients, 86.91% received at least one medication. Single-use hyaluronic acid (HA) was most commonly prescribed (43.0%), followed by bottled steroids (24.5%), bottled HA (19.6%), and bottled diquafosol (4.3%). Annual prescriptions of cyclosporine and single-use steroids increased over time. Older patients were more likely to receive bottled formulations than single-use medication. This is the first nationwide study to examine DED prescription patterns on a large-scale population basis in South Korea, and the findings highlight the accessibility of HA-based therapies within a universal health coverage system, offering a distinct perspective compared to global patterns.